Peran Guru Pai Dalam Membentuk Karakter Moderat Pencegah Radikalisme Di Sekolah - Abdul Halim Rais (STAI Kuala Kapuas, 2025)
Radicalism among students is a complex phenomenon influenced by both internal and external factors. Internally, identity exploration, narrow religious understanding, social dissatisfaction, and emotional influences contribute to students’ vulnerability to radical ideologies. Psychological aspects, such as academic pressure and emotional distress, further heighten this risk. Externally, social environment, social media, radical groups, and socio-political injustice play significant roles in shaping radical tendencies. The role of Islamic Religious Education (PAI) teachers is crucial in fostering moderate character and preventing radicalism. PAI teachers can achieve this by integrating moderation values into education, serving as role models, encouraging critical discussions, and acting as counselors. By promoting tolerance, critical thinking, and inclusive educational environments, PAI teachers help shape students into individuals who uphold moderation, reject extremism, and contribute positively to society. The study emphasizes the importance of comprehensive religious education and national awareness in countering radical influences among students